The legal environment of business and online commerce business ethics, e-commerce, regulatory, and international issues - Cheeseman, Henry R. (Pearson Education, 2010)
The sixth edition focuses on presenting the legal environment and ethics in a way that will spur students to ask questions and go beyond basic memorization. The cases in this text are cutting-edge, exciting, and engaging, and the reasoning of each case is presented in the language of the court.